Microanatomy of the enteric neurons and glia; expression patterns of the PGP9.5, S100b proteins, RET and SOX10 genes in the human fetal gut wall - Chacchu Bhattarai; Phanindra Prasad Poudel; Arnab Ghosh; Saman Man Pradhan; Nirmal Panthi; Dela Singh Joshi; Shanti Khadka; Sandhya Kumari; Guruprasad Kalthur; Vani Lakshmi R; Sujan Gautam; Sneha Guruprasad Kalthur (Translational Research in Anatomy)
Background: Enteric nervous system comprises enteric neurons and glia, derived from neural crest cells, and regulates the gastrointestinal function. Previous animal studies have highlighted the essential roles of RET and SOX10 genes, along with PGP9.5 and S100b proteins, in the development of neurons and glia. This study investigates the expression of these genes and proteins in the human fetal gut wall. Methods: Tissue samples of the human fetal gut wall were stained using haematoxylin and eosin, phosphotungstic acid haematoxylin, Beilschowsky silver, and Masson's trichrome to examine the histomorphology of neurons and glia. Immunohistochemistry and qPCR were used to analyse the expression of PGP9.5, S100b proteins, RET and SOX10 genes. Results: Human fetal stomach and small intestine showed diverse neuronal and ganglionic morphologies. Neuronal migration occurred from the serosa through the muscle layers to the submucosa throughout all trimesters. As fetal age advanced, the number of neurons and glia decreased in the serosa and increased in the muscle layers and submucosa. PGP9.5 showed strong expression in the serosa and moderate expression in the deeper layers of the colon during the first trimester. Its expression diminished in the serosa and intensified in the inner layers with advancing gestation. S100b followed a similar pattern but was absent in epithelium. Expression of RET and SOX10 genes increased during the second and third trimesters. Conclusion: The expression patterns of RET and SOX10 genes, and PGP9.5 and S100b proteins support their roles in the development of enteric neurons and glia in the human fetal gut wall.